Pharmacological, Phytochemical and Computational Studies on Prenylated Flavonoids and Pterocarpans From Erythrina Fusca Lour. (Bangladesh Journal of Botany, 2024)
In the present study, the dry powdered bark of Erythrina fusca was extracted with methanol. It was subjected to peripheral analgesic study using the acetic acid-induced writhing test in mice model and it demonstrated significant analgesic activity. The methanol extract was partitioned into n-hexane, chloroform and water-soluble fractions. Primarily, the chloroform fraction of the methanol extract was subjected to various chromatographic techniques and four major metabolites, Lupinifolin (1), Lupinifolin-4’-methyl ether (2), Sandwicensin (3) and Licoagrocarpin (4) were purified. Molecular docking studies of 1-4 against cyclooxygenase-2 (COX-2) enzyme suggest that they may interact with COX-2 at different levels. The pharmacokinetic and biological parameters of 1-4 were also checked through in silico tool to understand their drug-likeliness.Bangladesh J. Bot. 53(2): 305-311, 2024 (June)